Pendampingan Pada Pengelolaan Sampah Menjadi Berkah Menuju Lingkungan Bersih, Sehat, dan Asri Di Desa Brumbu - Siti Fahimah (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2019)
Garbage is a problem that is as small but also crucial in society, it is seen as insignificant because only waste is not important, but it becomes crucial if it can cause negative impacts such as careless disposal at times, sewers or riverbanks cause flooding, dumped on the road causing buildup. Therefore, in handling waste, it must be done wisely. In the village of Brumbun, it is considered as a community that is aware of cleanliness, so they need an assistance to localize waste, so that programs are carried out with echoes from